Exploring the thermodynamic description of a simulation of flocking birds - Mantzaris, Alexander V.; Domenikos, George-Rafael (Frontiers in Complex Systems, 2025)
This study presents an approach to analyzing a simulation of birds flocking as a thermodynamic system. The simulation of birds is produced using standard agent-based modeling and the thermodynamic variables for the states of the trajectory using statistical mechanics. The energy of the birds is defined, and from the distribution function, the entropy, internal energy, temperature, heat flux, and pressure are defined. The trajectory of the entropy decreases as the flocks increase clustering among each other, becoming denser. As a result, internal energy generally decreases (with minor oscillations), and an overall steady decrease of the cumulative heat flux is also observed. Pressure is observed to decrease as the simulation progresses with the increase of the volume. Overall, the system displays consistency with the expected trajectories of all the thermodynamics variables in a cooling process. Thus, through this thermodynamic definition, a more in-depth representation of the state space of the system is achieved. This description offers information about both the microscopic and macroscopic behaviors of the flocks and, importantly, an understanding about the exchange of energy/information between the flock and the external environment through the heat flux.